2021
DOI: 10.1155/2021/8352204
|View full text |Cite
|
Sign up to set email alerts
|

Tuning of Photoluminescence and Antibacterial Properties of ZnO Nanoparticles through Sr Doping for Biomedical Applications

Abstract: Sr-doped ZnO nanoparticles have been synthesized using a soft chemical method. The doping ratio of Sr is varied in the range of 0 at.%, 3 at.%, and 5 at.% to 7 at.%. X-ray diffractograms revealed that the samples had hexagonal (wurtzite) structure without a trace of any mixed phase. The average crystallite size of the nanoparticles (NPs) ranged from 39 to 46 nm. The average crystallite size was increased for the initial doping (3 at.%) of Sr ions, and further increase in the doping ratio reduced the particle s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…The increase in emission implies that the possibility of recombination of free excitons increases due to thermal annealing. 12,27 During the annealing process, because of the separation of donor bond excitons into free excitons, the recombination rate is increased.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The increase in emission implies that the possibility of recombination of free excitons increases due to thermal annealing. 12,27 During the annealing process, because of the separation of donor bond excitons into free excitons, the recombination rate is increased.…”
Section: Resultsmentioning
confidence: 99%
“…The increase in emission implies that the possibility of recombination of free excitons increases due to thermal annealing. 12,27 During the annealing process, because of the separation of donor bond excitons into free excitons, the recombination rate is increased. Further, it is observed that after annealing at 350 1C, an intense blue PL band is exhibited at around 468.9 nm from the crystalline ZnO NPs.…”
Section: Materials Advances Papermentioning
confidence: 99%
See 2 more Smart Citations
“…In earlier research, enhanced bacteria-killing capacity was discussed in ZnO nanoparticles [11]. Many researchers have examined and reported the antibacterial activity of ZnO [12,13].…”
Section: Introductionmentioning
confidence: 99%